A Review of the Impact of Consumerism, Recycling and Pollution: Evidence from Southeast Asia: 1999 to 2019 - CHUCHU, Tinashe; MAZIRIRI, Eugine Tafadzwa; MOTOTO, Lebogang (Journal of Environmental Management and Tourism, 2020)
Consumerism has been linked to recycling and pollution over a substantial period leading to a surge of research interest of the past 20 years. Most of this interest has focused on South East Asian countries, namely India and Indonesia, considered as having one of the most polluted capitals in the world. This therefore prompts the present study which reviewed literature on the impact of consumerism, recycling and pollution from Southeast Asia during the 1999 to 2019. The study adopted a qualitative approach in which grey literature was utilised in conjunction with industry secondary data on consumerism, recycling and pollution from selected South East Asian countries. Literature was obtained from popular databases that included Science direct, Emerald and Ebsco host. Common themes were identified, and recurring tends were noted. Numerous findings were recorded, however it stood-out that the impact of pollution across South East Asia is a challenge that continuous regardless of the efforts from the global community. In conclusion, an overall assessment was provided and further research suggestions on consumerism, recycling and pollution were proposed.